Durable soft neural micro-electrode coating by an electrochemical synthesis of PEDOT:PSS / graphene oxide composites. (1st August 2019) - Lee, Seunghyeon; Eom, Taesik; Kim, Min-Kyoung; Yang, Su-Geun; Shim, Bong Sup
Abstract: The biocompatible neural interface has been one of the most difficult challenges in developing implantable active neural prostheses for more than a decade. Either in recording neural signals, which delivers intelligent signals to operate active prostheses or in stimulating living tissues, which aids sensing organ deficits, neural electrodes play central roles in relaying information between biotic tissues and abiotic electronics. Until now no single material can possess all the ideal physicochemical properties of chronically implantable neural electrodes although organic conducting polymers have demonstrated the most promising functional integration with neural tissues. Here, we have successfully constructed poly(3, 4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)/graphene oxides (GOs) hybrid composites by electrochemical deposition on a gold micro-electrode. By changing the compositions and the redox states of GOs, the composites showed varied electrochemical performances as implantable neural electrodes, which have been further analyzed by Raman spectroscopy and scanning electron microscopy (SEM), and PC12 neural cellular attachment tests. Our experimental results indicated that both PEDOT:PSS/GOs and PEDOT:PSS/reduced graphene oxides (rGOs) were significantly better than PEDOT:PSS in electrochemical performances, mechanical softness, as well as favorable protein expressions of modulating PC12 neural cells. Therefore, our PEDOT:PSS/rGO composites can be used to further improve the PEDOT in the applications of an implantable electrode, biosensors, drug delivery carriers, and neural interfaces. Graphical abstract: Image 1 Highlights: The PEDOT:PSS/GO composites were deposited on the gold microelectrode for the applications of biocompatible soft neural interfaces. We have studied the electrochemical, mechanical, and biological performances as implantable electrodes by varying the compositions and the redox states of GOs. PEDOT:PSS/GO composites were better than PEDOT:PSS in electrochemical performances as well as favorable protein expressions of modulating PC12 cells. PEDOT:PSS/GO hybrid composites were not just cytocompatible but also able to modulate gene expression of specific proteins such as GAP-43 and synapsin.